Electrospun metal–organic framework-based nanofibers with natural therapeutic agents for enhanced diabetic wound healing - Yeoh, Soo Ghee; Liew, Yun Khoon; Low, May Lee; Lim, Wei Meng; Abdul Rahman, Norizah; Wong, Lai Chun; Then, Yoon Yee (Discover, 2025)
Diabetes mellitus (DM) poses a significant global health challenge, with diabetic foot ulcers (DFUs) standing as a serious consequence of this metabolic disorder. The intricate interplay of peripheral neuropathy, compromised blood supply, susceptibility to infections, and delayed healing processes in diabetic patients underscores the urgency for innovative wound management strategies. This review delves into the promising realm of electrospun metal–organic framework (MOF)-based nanofibers loaded with natural therapeutic agents, offering a multifaceted approach to accelerate diabetic wound healing by offering synergistic anti-inflammatory, anti-oxidant, and anti-bacterial properties. The incorporation of MOFs, characterized by their inorganic porous structures, alongside polymeric nanofibers, has the potential to enhance drug loading capacity and prevent burst release effect of nanofibers. This paper aims to provide a comprehensive understanding of the diabetic wound healing process, elucidate the properties of MOFs with exceptional porosity and high surface-to-volume ratios for extended and controlled drug release, and highlight the unique attributes of electrospun nanofibers in creating a conducive wound environment for tissue repair, re-epithelialization and vascularization. Additionally, this review explores seven natural therapeutic agents—borneol, clove essential oil, curcumin, chrysin, honey, aloe vera, quercetin, and rutin, showcasing their potential in diabetic wound care by enhancing the granulation tissue formation, collagen deposition, tissue remodeling and wound contraction. This comprehensive examination serves as a valuable resource for researchers and practitioners seeking advanced solutions for the management of diabetic foot ulcers.